Making geopolymer a temperature sensor - Tay, Bernie Wee Yuan (2019)
Thermoelectric effect is defined as the conversion of temperature differential to electrical voltage through a thermal couple. This is a useful property in a cementitious structure because it allows the structure to be able to self-monitor its temperature during a fire. When cementitious materials are exposed to fire, it loses its strength and spalling will occur. Thus, geopolymer is used as an alternative as it displays good fire resistance as compared to concrete. The change in the thermoelectric behavior of geopolymer under fire conditions has not been investigated so far. Therefore, this work focuses on the discovery of the thermoelectric behavior of geopolymer under high temperature and the inner mechanism would be disclosed in order to improve the material with the attainment of robust thermal self-monitoring function. Additionally, experimental set-ups have been enhanced in order to achieve better accuracies of voltage and temperature measurements.